An Integrated Adult Congenital Heart Disease Psychology Service. (26th February 2016) - Ferguson, Meaghan; Kovacs, Adrienne H.
Abstract: Objective: North American adults with congenital heart disease (CHD) are at increased risk of mood and anxiety disorders, although there are no published data on psychological treatment. In order to provide guidance to adult CHD (ACHD) programs considering the integration of psychological care, the aim of this study was to provide a comprehensive description of a specialized ACHD psychological service. Design: At a large tertiary hospital, a retrospective review of 100 ACHD clinic patient psychology files was performed. The following data were abstracted: sociodemographic and medical background, presenting psychological concerns, and the course and outcome of psychological intervention. Results: Of 100 patients, the mean age was 33 ± 11 years and 51% were female. Prevalent psychological concerns were generalized anxiety (82%), health‐/heart‐related anxiety (71%), depressed mood (60%), and difficulty coping with a medical condition (49%); 65% of patients met diagnostic criteria for a mood or anxiety disorder. Following assessment, individual psychotherapy was offered to 87 patients, of whom 75 opted to proceed with treatment. The median number of psychotherapy sessions was 8 and treatment most frequently included cognitive therapy (92%), relaxation skills training (57%), and communication skills training (46%). Of 64 patients for whom a course of psychotherapy had ended at the time of data abstraction, 54 (88%) had reduced or absent psychological distress. Conclusions: Reduced psychological distress can be achieved among adults with CHD who receive targeted psychological intervention. Consistent with the emerging field of behavioral cardiology, other ACHD programs as well as general cardiovascular programs are encouraged to integrate cardiac psychology services in order to provide comprehensive patient care.